Review of ICD-10 Differences Chapter 5 Mental and Behavioral Disorders with DSM-5 - Budiyanti, Nita; Dewi Rahmawati, Fitria; Sofiyah, Sofiyah (Jurnal Medisci, 2023)
ICD-10 Chapter 5 "Mental and Behavioral Disorders" is used to record the diagnoses of all patients seen in psychiatric treatment. The DSM-5 is the standard classification of mental disorders used by mental health professionals in the United States. The differences in determining the diagnosis code in ICD-10 Chapter 5 Mental and Behavioral Disorders and DSM-5 can be influenced by the basic structure coding rules that follow in both classification systems. The purpose of this study was to determine the differences in the basic structure of ICD-10 Chapter 5 Mental and Behavioral Disorders with DSM-5. This research design uses literature review. The results of this study show that there are differences, among others, in the definition of the terms include and exclude in ICD-10 and DSM-5. Koder must improve the ability to understand definitions in the process of determining the codification of the two classification systems.